Predicted climate conditions and cover crop composition modify weed communities in semiarid agroecosystems. (22nd November 2021) - DuPre, Mary E.; Seipel, Tim; Bourgault, Maryse; Boss, Darin L.; Menalled, Fabian D.
Abstract: The US Northern Great Plains is one of the largest expanses of small grain agriculture, but excessive reliance on off‐farms inputs and predicted warmer and drier conditions hinder its agricultural sustainability. In this region, the use of cover crops represents a promising approach to increase biodiversity and reduce external inputs; however little information exists about how cover crop mixture composition, predicted climate and management systems could impact the performance of cover crops and weed communities. In the 4th cycle of a cover crop‐wheat rotation, we experimentally increased temperature and reduced moisture as expected to occur with climate change, and assessed impacts on the presence and composition of cover crop mixtures and termination methods on weed communities. Under ambient climate conditions, mean total cover crop biomass was 43%–53% greater in a five species early‐season cover crop mixture compared with a seven species mid‐season mixture, and differences were less pronounced in warmer and drier conditions (19%–24%). We observed a total of 18 weed species; 13 occurring in the early‐season mixture, 13 in the mid‐season mixtures and 14 in the fallow treatments. Weed species richness and diversity was lower in warmer and drier treatments, and we observed a shift in weed communities due to the presence and composition of cover crop mixtures as well as climate manipulations. Overall, results suggest that adoption of cover crop mixtures in semiarid agroecosystems requires jointly addressing weed management and soil moisture retention goals, a challenge further complicated by predicted climate conditions.